A Reponse to the Paper by Prof Aquiline Tarimo, “Culture, Ethnicity, and Democracy” (Hekima Review, 2013)
This paper seems to be concerned with the democratization process introduced to Africa in late 1980s and early 1990s but which had insignificant impact on the continent. Its indicator, the multiparty democracy, which was expected to transform political power only led to destructive competition for leadership, lack of guarantee for the participation of the masses in the political process, failure to promote a democratic culture. He intimates that the ground was not adequately prepared to embrace the democratic process whose values can only be promoted when local conditions of life, value systems and civic education has been undertaken. This means that the introduction of democracy is a process not an event.